Conservation of stored food using plant's extracts. Effect of oregano (Origanum vulgaris) essential oils on the reproduction and development of flour moth (Ephestia kuehniella) - Taibi, Faiza; Boumendjel, Mahieddine; Moncef, Zaafour; Omar, Sekiou; Taha, Khaldi; Amel, Delimi; Safa, Abdessmad; Hassiba, Rebani; Hanène, Chnouga; Nacira, Siakhène; Amel, Boumendjel; Mahfoud, Messarah (Cellular and Molecular Biology, 2018)
In the search for effective methods of biological control of stored products insect-pests, the essential oil of Origanum vulgaris was extracted using Clevenger apparatus and tested on reproduction and mortality of flour moth Ephestia kuehniella. Bio-insecticide works with a double action mechanism; administered by inhalation in pupae, essential oil affects their pupal development. It also disrupts the reproduction of exuviated adults by extending the preoviposition period and reducing the period of egg laying and fecundity because fecundated females cannot live more than four days compared to control group. Moreover, the essential oil administered by inhalation in adults causes a significant mortality rate compared to control group by reducing their lifespan. A repellent effect against larvae and adults of this pest was noticed in this work. This allowed us ranking this oil as "moderately repulsive".